2021
DOI: 10.1158/0008-5472.can-19-3911
|View full text |Cite
|
Sign up to set email alerts
|

A High-Content Screen Identifies Drugs That Restrict Tumor Cell Extravasation across the Endothelial Barrier

Abstract: Metastases largely rely on hematogenous dissemination of tumor cells via the vascular system and significantly limit prognosis of patients with solid tumors. To colonize distant sites, circulating tumor cells must destabilize the endothelial barrier and transmigrate across the vessel wall. Here we performed a high-content screen to identify drugs that block tumor cell extravasation by testing 3,520 compounds on a transendothelial invasion coculture assay. Hits were further characterized and validated using a s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Therefore, we tested whether Imatinib prevents endothelial cell monolayer disruption by seeding MDA-MB-231 tumor cells into the microvessel perfusion channel with a confluent monolayer of HUVECs in OrganoPlate ® . Tumor cells adhered to the endothelium and progressively disrupted the endothelial barrier by dislodging endothelial cells and cell expansion over 72 hours, as previously described (46). We found that the endothelial cell number and endothelium area were preserved more in the Imatinib-treated chips than in controls (Figure 6B), and many tumor cells remained on the endothelium surface in Imatinibtreated chips.…”
Section: Effect Of Imatinib On Vascular-mediated Mechanisms Of Cancer...supporting
confidence: 83%
“…Therefore, we tested whether Imatinib prevents endothelial cell monolayer disruption by seeding MDA-MB-231 tumor cells into the microvessel perfusion channel with a confluent monolayer of HUVECs in OrganoPlate ® . Tumor cells adhered to the endothelium and progressively disrupted the endothelial barrier by dislodging endothelial cells and cell expansion over 72 hours, as previously described (46). We found that the endothelial cell number and endothelium area were preserved more in the Imatinib-treated chips than in controls (Figure 6B), and many tumor cells remained on the endothelium surface in Imatinibtreated chips.…”
Section: Effect Of Imatinib On Vascular-mediated Mechanisms Of Cancer...supporting
confidence: 83%
“… 39 In addition, forskolin treatment of endothelial barriers rescued the tumor cell-induced hyperpermeability and decreased the transendothelial migration of pancreatic cancer cells. 40 Forskolin is a widely used inducer of cyclic adenosine monophosphate (cAMP)-driven PKA activation. 35 PKA activity in mesothelial cells regulates inflammatory response as evidenced by a previous study that demonstrated PKA-dependent shedding of tumor necrosis factor receptors upon stimulation with interleukin-1-α.…”
Section: Discussionmentioning
confidence: 99%
“…It allows comprehensive recording of phenotypic changes and quantifies different morphological parameters by segmenting cell images using intelligent algorithms. In recent years, HCS has been used for drug screening, virus infection, toxicology and tumor migration studies [ 28 , 29 , 30 , 31 , 32 ]. Therefore, HCS is an appropriate system for the quantification of cell morphological changes during the EMT allowing distinction of the inhibitory effects of different compounds on this process.…”
Section: Discussionmentioning
confidence: 99%